Islamic instruments in treating and mitigating the mortgage – Crisis Malaysia Capital Market Case Study 2007/2016 – - leila, Achoub; lilia, Ghedabna (Journal of Economic, Administrative and Legal Sciences, 2021)
In light of the increasing interest and development of Islamic financial architecture, especially after the 2008 mortgage crisis and its innovative products and financial instruments such as Islamic Sukuk, , Not to mention its important and large role in reducing the big difference between the financial economy and the real economy, we decided In our research, to study the role of Islamic sukuk in dealing with the global financial crisis 2008, by studying the state of Malaysia, especially as the latter is among the first countries in the field of Islamic financial market activity.